Pertanggungjawban Hukum Bisnis terhadap Pihak Ketiga dalam Transaksi Bisnis Internasional Sesuai dengan Prinsip Good Corporate Govermance - Esa Brilian Madina; Rani Apriani (Jurnal Hukum Lex Generalis, 2024)
This research discusses the implementation of Good Corporate Governance (GCG) principles in ensuring business legal liability towards third parties in international business transactions. The discussion focuses on how the principles of Good Corporate Governance, such as transparency, accountability, and independence, play a role in maintaining the integrity of the company and protecting the interests of third parties, such as consumers and business partners. The results show that effective implementation of Good Corporate Governance principles can increase public trust and maintain the sustainability of international business relationships. In conclusion, companies must integrate Good Corporate Governance principles in every aspect of operations to ensure legal compliance and business sustainability.